Respuestas

2012-10-06T04:54:06+02:00

x+0+z=-2

x=-z-2


0+y-z=3

y-z


x-y+0=1

x=y+1



ojala sea esto para poderte ayudar

2012-10-06T04:55:30+02:00

x+0+z=-2                               0+y-z=3        x-y+0=1

x+z=-2                                   y-z=3            x-y=1

y-z=3 sumas los dos

 

x+z+y-z=3-2

x+y=1

x-y=1   sumas los dos

 

2x=2

x=1  reemplazas el x      x-y=1   

                                    1-y=1

                                    y=0

y-z=3   reemplazas el y

 

0-z=3

z=-3

 

SUERTE!!!!!!!1111